2022
DOI: 10.1186/s13148-022-01302-x
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive early detection of colorectal cancer by hypermethylation of the LINC00473 promoter in plasma cell-free DNA

Abstract: Background Current noninvasive assays have limitations in the early detection of colorectal cancer. We evaluated the clinical utility of promoter methylation of the long noncoding RNA LINC00473 as a noninvasive biomarker to detect colorectal cancer and associated precancerous lesions. Methods We evaluated the epigenetic regulation of LINC00473 through promoter hypermethylation in colorectal cancer cell lines using bisulfite genomic sequencing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Since the first immortalized cell line (HeLa) was established 25 , human cancer-derived cell lines have been demonstrated to be fundamental models used in laboratories for many years to understand the biology of cancer and pursue clinical applications 21 , 26 , 27 . Recent findings based on the characterization of hundreds of cell lines with omics technologies reinforced the concept of cell line usefulness in medical research 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the first immortalized cell line (HeLa) was established 25 , human cancer-derived cell lines have been demonstrated to be fundamental models used in laboratories for many years to understand the biology of cancer and pursue clinical applications 21 , 26 , 27 . Recent findings based on the characterization of hundreds of cell lines with omics technologies reinforced the concept of cell line usefulness in medical research 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Other reports demonstrated that LINC00473 is downstream of the fusion oncoprotein CRTC1-MAML2 in mucoepidermoid carcinoma, and that the deletion of CRTC2/3 leads to decreased levels of LINC00473 [ 48 , 64 ]. In contrast, LINC00473 was discovered to be transcriptionally silenced due to promoter hypermethylation in colorectal cancer and was suppressed in osteosarcoma cells by the direct binding of ZBTB7A (encoding Pokemon) to the LINC00473 promoter [ 50 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the discovery of novel therapeutic targets is of utmost importance for enhancing the treatment of CRC. There is also a pressing need for non-invasive diagnostic tools to reduce the mortality rates associated with CRC [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%